Influence of some biologically active substances on amount of MGMT and MARP proteins in human cells in vitro - Kotsarenko, K.V.; Lylo, V.V.; Macewicz, L.L.; Ruban, T.P.; Luchakivska, Yu.S.; Kuchuk, M.V.; Lukash, L.L. (Вiopolymers and Cell, 2014)
Aim. To investigate an effect of biologically active compounds IFN-α2b, EMAPII, Card medium, fibronectin on the amount of MGMT (O6-methylguanine-DNA methyltransferase) and MARP (anti-Methyltransferase Antibody Recognizable Protein) proteins in human cells in vitro. Methods. The human cells of 4BL, Hep-2 and A102 lines were treated with growth factors and cytokines. Changes in the amount of MGMT and MARP proteins were studied by Western blot analysis with anti-MGMT mAbs. Results. The treatment of A102 cells with EMAPII, fibronectin, Laferon and Card medium led to a decreased level of the MGMT protein, whereas the amount of MARP was highly increased in these cells. The treatment with the recombinant protein IFN-α2b increased the amount of MGMT and MARP proteins in Hep-2 cells. The treatment with extracts of transgenic plants,containing human IFN-α2b, caused a significant decrease in the content of both proteins in Hep-2 cells and MARP in 4BL cells. Conclusions. Both MGMT and MARP are highly inducible proteins. Their amount in cells can be changed by some growth factors (Card medium, fibronectin), cytokine (IFN-α2b), cytokine-like (EMAPII) or cytokine-containing substances (Laferon and IFN-α2b in plant extracts). This regulation depended not only on the type of biologically active substances but on the cell line used in this study as well. Мета. Дослідження впливу біологічно активних сполук IFN-α2b, EMAPII, середовища Card і фібронектину на вміст білків MGMT (О6-метилгуанін-ДНК метилтрансфераза) і MARP (білок, що розпізнається анти-MGMT антитілами) у клітинах людини in vitro. Методи. Клітини людини ліній 4BL, Hep-2 і A102 обробляли ростовими факторами і цитокінами. Зміни в кількості білків MGMT і MARP досліджували з використанням Вестерн блот аналізу і моноклональних анти-MGMT антитіл. Результати. Обробка клітин A102 препаратами EMAPII, фібронектину і Лаферону призводить до зниження кількості білка MGMT на фоні значного зростання кількості білка MARP у цих клітинах. Обробка рекомбінантним білком IFN-α2b підвищує кількість білків MGMT і MARP у клітинах Hep-2, а екстрактами трансгенних рослин, які містять IFN-α2b людини, – зменшує кількість обох білків у клітинах Hep-2 та білка MARP у клітинах 4BL. Висновки. MGMT і MARP є високо-індуцибельними білками. Їхня кількість може варіювати під дією деяких ростових факторів (середовище Card і фібронектин), цитокіну (IFN-α2b), цитокіноподібного (EMAPII) та цитокіновмісних (Лаферон і IFN-α2b у композиції з рослинними екстрактами) препаратів. Виявлена регуляція залежить не лише від типу біологічно активних речовин, але й від клітинних ліній, використаних в експериментах. Цель. Исследовать влияние биологически активных соединений IFN-α2b, EMAP II, среды Card и фибронектина на содержание белков MGMT (О6-метилгуанин-ДНК метилтрансфераза) и MARP (белок, распознаваемый анти-MGMT антителами) в клетках человека in vitro. Методы. Клетки человека линий 4BL, Hep-2 и A102 обрабатывали ростовыми факторами и цитокинами. Изменения в количестве белков MGMT и MARP исследовали с использованием Вестерн блот анализа и моноклональных анти-MGMT антител. Результаты. Обработка клеток А102 препаратами EMAPII, фибронектина, Лаферона и среды Card снижает количество белка MGMT на фоне значительного возрастания количества белка MARP в этих клетках. Обработка рекомбинантным белком IFN-α2b увеличивает количество белков MGMT и MARP в клетках Hep-2, а экстрактами трансгенных растений, содержащих человеческий IFN-α2b, – существенно снижает количество обоих белков в клетках Hep-2 и MARP в клетках 4BL. Выводы. MGMT и MARP являются высокоиндуцибельными белками. Их количество может варьировать под действием некоторых ростовых факторов (среда Card и фибронектин), цитокина (IFN-α2b) цитокиноподобного (EMAP II) и цитокинсодержащих (Лаферон и IFN-α2b в композиции с растительными экстрактами) препаратов. Выявленная регуляция зависит не только от типа биологически активных веществ, но и от клеточных линий, использованных в экспериментах.